Semi-Annual Report, 2016 - Kansas State University; University of Illinois; Oklahoma State University; University of Kentucky; University of Nebraska – Lincoln; South Carolina State University; Ft. Valley State University; USDA-ARS Center for Grain and Animal Health Research (My University, 2017)
The Feed the Future Innovation Lab for the Reduction of Post-Harvest Loss (PHLIL) is a strategic, applied, research and education program aimed at improving food security by reducing post-harvest loss and food waste of seeds and durable staple crops, e.g., grains, oilseeds, and legumes. The Lab’s efforts are focused in four Feed the Future countries (Bangladesh, Ethiopia, Ghana, and Guatemala) and Afghanistan.
Feed the Future Innovation Lab for the Reduction of Post-Harvest Loss. October 2015 - March 2016
Keywords: Innovation Lab; Post-Harvest Loss; Food Waste; Durable Staple Crops; Crop Seeds